Cadangan Reklamasi Pertambangan Sebagai Loopholes Pajak dalam Penerapan Prinsip Taxability-Deductibility - Chairil Anwar Pohan (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2014)
Ironic look messy mining face in this country and so much troublesome services of government officials, especially in the mining region of area businesses amid rampant mining minerals (Gold, Tin, Copper, Nickel, etc.) and coal were carried out by the Investor, the resultant investment offers little value added contribution on state revenues, whereas post-exploitation or post-mining closure leaves holes gaping tailings left just by miners, resulting in environmental degradation, social inequality and other things that have a negative impact that brings enormous material losses for the country and society, which never should have happened because of the taxation aspects of the government actually had anticipated that the mining activities should be facilitated by the provisioning cost of reclamation in mining production activities are underway, the reserve for reclamation explicitly accommodated as accounts exclusion in Article 9, paragraph 1 of Income Tax Law, that the taxation treatment is a cost that can be a deduction from gross income.